PENGARUH LINGKUNGAN KERJA, KEPEMIMPINAN DAN KOMUNIKASI INTERPERSONAL TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. RAJAWALI HIYOTO - Ingrit Novalina Br. Sitinjak; Tika Nirmala Sari (Jurnal Widya, 2024)
This research aims to determine the influence of the work environment, leadership and interpersonal communication on employee job satisfaction at PT. Rajawali Hiyoto. The number of samples used in this research was 62 respondents. The data collection techniques used in this research used observation, questionnaires and interviews. The testing techniques used in this research use research instrument tests, descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis tests. The test results concluded from the partial test are that the work environment variable has no significant positive effect on employee job satisfaction, while the leadership and interpersonal communication variables have a significant positive effect on employee job satisfaction. Simultaneous test results showed that together the work environment variables leadership and interpersonal communication affected employee job satisfaction.